CULTURE SHOCK DAN AKULTURASI DALAM LINGKUNGAN BUDAYA BELANDA - Sulih Indra Dewi (Universitas Tribhuwana Tunggadewi, 2013)
Au pair for some Indonesian people is still a strange term, but this program is getting popular nowadays among Indonesian young women. This program gives opportunities to learn language, culture and also valuable life experiences. The Netherlands as one of the destination countries offers challenges for the participants to cope with cultural differences. The participants have experienced cultural friction and how they survived during the period of time, which is the focus of the study. This research used descriptive qualitative research method in collecting data by direct observation, participative, in depth interview and documentation. The respondents were taken with purposive sampling technique. To measure the data validity, the researcher used trust degree technique, there are peer debriefing and triangulation. Next, the data analysis used Miles and Huberman (1992) interactive data analysis which consist of data reduction, data display, conclusion withdrawal and verification.This study finally revealed some important result as follow: (1) The biggest motivation to join this program is getting experience living abroad; (2) All of the participants of this program experienced culture shock about food, life style and weather during their stay; (3) The internal factor and external factor helped the participants to acculturate in Dutch culture; (4) In general the smaller and shorter culture shock of the participants the easier acculturation process.